An experimental study of gaseous exhaust emissions of diesel engine using blend of natural fatty acid methyl ester - Sudrajad, Agung; Ismail, Ali; Samo, Khalid; Faturachman, Danny (IOP Publishing, 2012)
Vegetable oil form in Natural Fatty Acid Methyl Ester (FAME) has their own advantages: first of all they are available everywhere in the world. Secondly, they are renewable as the vegetables which produce oil seeds can be planted year after year. Thirdly, they are friendly with our environment, as they seldom contain sulphur element in them. This makes vegetable fuel studies become current among the various popular investigations. This study is attempt to optimization of using blend FAME on diesel engine by experimental laboratory. The investigation experimental project is comparison between using blend FAME and base diesel fuel. The engine experiment is conducted with YANMAR TF120M single cylinder four stroke diesel engine set-up at variable engine speed with constant load. The data have been taken at each point of engine speed during the stabilized engine-operating regime. Measurement of emissions parameters at difference engine speed conditions have generally indicated lower in emission NOx, but slightly higher on CO2 emission. The result also shown that the blends FAME are good in fuel consumption and potentially good substitute fuels for diesel engine.